Glycated hemoglobin level on admission associated with progression to severe disease in hospitalized patients with non‐severe coronavirus disease 2019 - Ryutaro Numaguchi; Masafumi Kurajoh; Yoshikazu Hiura; Takumi Imai; Tomoaki Morioka; Mika Saito; Satoshi Shiraishi; Masanori Emoto; Yukio Nishiguchi (Journal of Diabetes Investigation, 2022)
Abstract Aims/Introduction Poor glycemic control is known to be associated with severe infection development. This retrospective observational study examined whether glycemic control before coronavirus disease 2019 (COVID‐19) onset contributes to progression from non‐severe to severe COVID‐19. Materials and Methods Glycated hemoglobin (HbA1c) was measured on hospital admission in 415 patients with non‐severe COVID‐19. The outcome was determined from time of hospital admission to severe progression, based on clinical practice guidelines for COVID‐19 in Japan. Results The median value for HbA1c on admission was 6.1%, with diabetes present in 138 patients (33.3%). Among the total cohort, 93 (22.4%) progressed to severe COVID‐19 with a median (interquartile range) time of 4 days (3–7 days), whereas 322 (77.6%) were discharged after 13 days (10–17 days). A multivariable Cox proportional hazards regression model showed that HbA1c level on admission was independently associated with progression to severe COVID‐19 (hazard ratio for 1% increase 1.237, 95% confidence interval 1.037–1.475; P = 0.018), with findings consistent among several sensitivity analyses. In subgroup analyses, such an association was significant in patients with diabetes, as well as older age, current smoking habit, lower estimated glomerular filtration rate, higher C‐reactive protein level, moderate II COVID‐19, dyslipidemia and chronic respiratory disease, with no remarkable inconsistency among the subgroups. Finally, higher HbA1c level (≥7%) was more strongly associated with severe COVID‐19 progression than diabetes. Conclusions The results suggest that poor glycemic control before COVID‐19 onset contributes to progression from non‐severe to severe COVID‐19, even in patients with severe COVID‐19 risk factors regardless of the presence of diabetes.